2020
DOI: 10.1016/j.celrep.2020.108402
|View full text |Cite
|
Sign up to set email alerts
|

Functional Specialization of Human Salivary Glands and Origins of Proteins Intrinsic to Human Saliva

Abstract: Highlights d Genes encoding highly abundant secreted proteins define adult gland types d Gland-specific activity of transcriptional regulators contributes to proteome diversity d Differential retention of fetal genes drives functional diversity in adult glands d Cellular heterogeneity underlies gland-specific protein secretions

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 117 publications
(150 reference statements)
2
75
0
Order By: Relevance
“…CC-BY-NC-ND 4.0 International license made available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is The copyright holder for this preprint this version posted March 6, 2021. ; https://doi.org/10.1101/2021.03.05.433813 doi: bioRxiv preprint [27,28]. Lectin (carbohydrate-binding proteins), including conglutinin, SP-D, MBL, and SAP, bind selectively to specific carbohydrate structures (mannose-over galactosetype sugars) located at the head of the influenza HA of susceptible strains, thereby blocking the ability of HA to bind to sialylated cell-surface receptors [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CC-BY-NC-ND 4.0 International license made available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is The copyright holder for this preprint this version posted March 6, 2021. ; https://doi.org/10.1101/2021.03.05.433813 doi: bioRxiv preprint [27,28]. Lectin (carbohydrate-binding proteins), including conglutinin, SP-D, MBL, and SAP, bind selectively to specific carbohydrate structures (mannose-over galactosetype sugars) located at the head of the influenza HA of susceptible strains, thereby blocking the ability of HA to bind to sialylated cell-surface receptors [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that sialic acid-independent factors are also involved in anti-IAV activity. One of the possible factors is the action of lectin-like proteins, such as ZG16B, which have shown a high correlation with anti-IAV activity [27,28]. Lectin (carbohydrate-binding proteins), including conglutinin, SP-D, MBL, and SAP, bind selectively to specific carbohydrate structures (mannose-over galactosetype sugars) located at the head of the influenza HA of susceptible strains, thereby blocking the ability of HA to bind to sialylated cell-surface receptors [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Why venom isn't more common in mammals despite the high tissue specificity of venom homologs, or why venom homologs have less tissue specificity in some reptiles can be because of numerous factors. For example, perhaps selective pressures in mammals lead to an increase in regulatory complexity (for multifunctionality) in oral tissues rather than increasing dosage of a few (toxicopotent) components (Saitou et al 2020) . Or perhaps non-venomous reptiles occupied stable niches where evolution of a venom system wasn't required.…”
Section: Evolution Of Tetrapod Venoms By Kallikrein Exaptationmentioning
confidence: 99%
“…Salivary proteins facilitate food perception and digestion, maintain the integrity of mineralized tooth and oral epithelial surfaces, shield the oral digestive tract from environmental hazards and invading pathogens, and protect oral tissues from fungal or viral infections [4,5]. Moreover, it is suggested that the origins of salivary proteins can be analyzed throughout mixed saliva and that post-transcriptional modifications may play a key role in understanding secretome network pathways [6,7]. Moreover, Feizi et al, 2020 [7] found that the study of secretion pathways (translocation, folding, trafficking and glycosylation) is relevant to know tissue-specific secretion pathways and tissuespecific secretomes that would facilitate the elaboration of a link between proteins and diseases.…”
Section: Introductionmentioning
confidence: 99%